Parkinson’s Disease, Symptoms, Manifestation, Treatment Methods - Popa, Oana (New Trends in Psychology, 2022)
Parkinson’s disease, as established in 1960 by scientists When Ehringer and Hornykiewic, is a disorder of the brain caused by the destruction or degeneration of dopamine-producing neurons (a neurotransmitter responsible for the body’s ability to control its movements. Parkinson’s disease is found in 0.3% in the general population, with an exponential growth trend with age: 1.5% in the population aged 65. The diagnosis is usually made by the doctor, who records the patient’s medical history and submits it. Clinical examination This symptom is manifested by stiffening of the affected areas of the body Stiffness becomes apparent when the affected arm or leg is moved by the examiner Older people are more prone to injury from obstruction due to osteoporosis and reduced muscle strength. In patients with Parkinson’s disease, this problem is seconded by the fact that the reflexes of important protection may be lacking, such as stretching the arms in the event of a fall or rolling the torso. Through the various therapies currently available, the symptoms of Parkinson’s disease can be alleviated. Parkinson’s therapy falls into three major categories.